Morpheme of Heartbreak in Taylor Swift’s The Tortured Poest Department Album - Ulfiyanti, Fika; Eryon, Eryon; Samanik, Samanik (Kajian Linguistik dan Sastra, 2026)
This study aims to analyze morphemic changes through the process of derivation in the lyrics of songs on Taylor Swift's The Tortured Poets Department, as well as explain the emotional and artistic functions that arise from these changes. The focus of the research includes three songs, namely But Daddy I Love Him, Fortnight, and Guilty as Sin?. The method used is qualitative descriptive with a morphological approach to identify forms of derivation, as well as an analysis of emotional and aesthetic meaning based on the stylistic theory of Leech (1981) and the conceptual metaphor of Lakoff and Johnson (1980). The results show that the use of prefixes (un-, dis-, a-) and suffixes (-y, -ful, -ous, -ing, -al, -ly, -ity, -er, -ic, -less, -ify, -ry) Not only does it change the class of words, but it also enriches the emotional meaning and artistic imagery in the lyrics. Derivation is used as a poetic strategy to describe inner conflicts, emotional vulnerability, and the dynamics of personal relationships in musical works. Thus, derivation serves not only grammatically but also as a means of creative expression that connects the structure of language with emotional experience in popular music.  Abstrak Penelitian ini bertujuan untuk menganalisis perubahan morfem melalui proses derivasi dalam lirik lagu pada album The Tortured Poets Department karya Taylor Swift, serta menjelaskan fungsi emosional dan artistik yang muncul dari perubahan tersebut. Fokus penelitian meliputi tiga lagu, yaitu But Daddy I Love Him, Fortnight, dan Guilty as Sin?. Metode yang digunakan adalah deskriptif kualitatif dengan pendekatan morfologi untuk mengidentifikasi bentuk-bentuk derivasi, serta analisis makna emosional dan estetik berdasarkan teori stilistika Leech (1981) dan metafora konseptual Lakoff dan Johnson (1980). Hasil penelitian menunjukkan bahwa penggunaan prefiks (un-, dis-, a-) dan sufiks (-y, -ful, -ous, -ing, -al, -ly, -ity, -er, -ic, -less, -ify, -ry) tidak hanya mengubah kelas kata, tetapi juga memperkaya makna emosional dan citraan artistik dalam lirik. Derivasi digunakan sebagai strategi puitis untuk menggambarkan konflik batin, kerentanan emosional, serta dinamika hubungan personal dalam karya musik. Dengan demikian, derivasi berfungsi tidak hanya secara gramatikal, tetapi juga sebagai sarana ekspresi kreatif yang menghubungkan struktur bahasa dengan pengalaman emosional dalam musik populer.